High resistance against clindamycin, metronidazole and amoxicillin in Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans isolates of periodontal disease (2010)
ABSTRACT: Objectives: To test the antimicrobial sensitivity of two periodontal pathogens to a panel of five orally administrable antibiotics in periodontal disease. Study design: A total of 69 isolates of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis were processed using culture and biochemical tests. Selected colonies of A. actinomycetemcomitans and P. gingivalis were used to evaluate the antibacterial activity of clindamycin, metronidazole, amoxicillin, moxifloxacin and amoxicillin/clavulanic acid. Results: Susceptibility testing revealed a sensitivity of 100% of A. actinomycetemcomitans and P. gingivalis to moxifloxacin and amoxicillin/clavulanic acid but moderate susceptibilities were found for the rest of antibiotics agents evaluated. Conclusions: The widespread use of antibiotics is reflected in the level of resistance of A. actinomycetemcomitans and P. gingivalis in patients with periodontal infections. This suggests that antibiotic susceptibility testing is necessary to determine efficacy of antimicrobial agents. Clinical studies with antibiotics should take these differences into account.